Volume overload induces autophagic degradation of procollagen in cardiac fibroblasts. (December 2015) - Fu, Lianwu; Wei, Chih-Chang; Powell, Pamela C.; Bradley, Wayne E.; Collawn, James F.; Dell'Italia, Louis J.
Abstract: In a pure volume overloaded (VO) heart, interstitial collagen loss is degraded by matrix metalloproteinases (MMPs) that leads to left ventricular (LV) dilatation and heart failure. Cardiac fibroblasts are the primary source of extracellular matrix proteins that connect cardiomyocytes. The goal of this study was to determine how VO affects intracellular procollagen in cardiac fibroblasts. Using the aortocaval fistula (ACF) model in Sprague–Dawley rats, we demonstrate that cardiac fibroblasts isolated from 4 and 12 wk ACF animals have decreased intracellular procollagen I compared to the fibroblasts from age-matched shams. The reduction of procollagen I is associated with increased autophagy as demonstrated by increased autophagic vacuoles and LC3-II expression. To test the relationship between autophagy and procollagen degradation, we treated adult cardiac fibroblasts with either an autophagy inducer, rapamycin, or an inhibitor, wortmannin, and found that procollagen I protein levels were decreased in fibroblasts treated with rapamycin and elevated in wortmannin-treated cells. In addition, we demonstrated that VO induces oxidative stresses in cardiac fibroblasts from 4 and 12 wk ACF rats. Treatment of cultured cardiac fibroblasts with an oxidative stress-inducing agent (DMNQ) induces autophagy and intracellular procollagen I and fibronectin degradation, which is reversed by wortmannin but not by the global MMP inhibitor (PD166793). Mechanical stretch of cardiac fibroblasts also induces oxidative stress and autophagic degradation of procollagen I and fibronectin. Our results suggest that in addition to the well-known effects of MMPs on extracellular collagen degradation in VO, there is a concurrent degradation of intracellular procollagen and fibronectin mediated by oxidative stress-induced autophagy in cardiac fibroblasts. Highlights: Volume overload induces oxidative stress and autophagy in cardiac fibroblasts from 4 and 12 wk aortocaval fistula rats. ACF rats have decreased intracellular procollagen in cardiac fibroblasts. The intracellular procollagen degradation is mediated through autophagy and is induced by oxidative and mechanical stresses. Both intracellular procollagen degradation by autophagy and interstitial collagen breakdown by MMPs cause the ECM loss in VO.